PENGATURAN KECEPATAN MOTOR INDUKSI 3 FASA MENGGUNAKAN MULTILEVEL INVERTER DENGAN METODE FUZZY LOGIC CONTROLLER - Maulana Malik Ibrahim; Moch. Rafi Damas Abdilla; Feby Chandra Arsandi (Jurnal Teknologi Terpadu, 2023)
Indonesia is one of the developing countries in the industrial sector. Many industrial equipment that utilizes an electric motor to run the system. In running the system using an electric motor, it is necessary to adjust the speed of the electric motor as needed. The 3-phase induction motor is one type of electric motor that has a strong, inexpensive, and high-efficiency construction, so it is often used in industry. However, setting the speed and torque of an induction motor is not easy to do. Setting the frequency of the induction motor voltage can be done using an inverter, therefore a single phase inverter can be used to adjust the speed of a three phase induction motor. In regulating the speed of the induction motor, a control is needed to keep the speed constant as needed. In this study, a 3-phase induction motor speed regulation system was simulated using an inverter controlled by a Fuzzy Logic Controller (FLC). Based on the research that has been done, it can be seen that the Fuzzy Logic Controller (FLC) is able to regulate the speed of a 3-phase induction motor with an error of 0.25%